Psychometric properties of a Creole version of Medical Outcome Study – Short Form 36 among type II diabetes patients on Reunion Island - Soulaimana, Ibtissame; Bruneau, Léa; Tisseaux, Antoine; Safieddine, Maissa; Debussche, Xavier; Lafarge, Sophie; Falissard, Bruno; Ferdynus, Cyril; Huiart, Laetitia (Frontiers in Public Health, 2023)
Introduction Health quality of life assessment is particularly important to measure the impact of chronic diseases. The aims of this study were to provide a cross-culturally adapted Creole-translation of the Medical Outcome Study Short-Form 36 (SF-36) and to assess psychometric performance of the Creole and French versions of the SF-36 among patients with type II diabetes in Reunion Island. Materials and methods The Creole translation and cross-cultural adaptation processes were based on the International Quality Of Life Assessment (IQOLA) methods. Internal consistency, test–retest reliability, convergent and discriminant validity using Multi-Trait-Multi-Method analysis and structural validity using exploratory factor analysis of the SF-36 for both versions were performed. Results In the Creole version of the SF-36, Cronbach’s alpha exceeded 0.70 for all subscales except general health. In the French SF-36, Cronbach’s alpha exceeded 0.70 on all subscales except general health and bodily pain. In the Creole SF-36, intraclass correlation coefficient (ICC) for reproducibility was suboptimal. Multi-trait multi-method analysis showed that item-scale correlation exceeded 0.4 for all items except two general health items of the Creole SF-36 and one of the French SF-36. Factor analysis of 2 versions showed that the physical functioning, vitality, and mental health were each divided into two subscales. Discussion Overall, our findings provided evidence that the SF-36 is adapted to Reunion Island in both Creole and French versions. However, further research could be conducted to investigate French–Creole differences in perceived health status and a cultural adaptation of the French version will be considered.